An investigation into the effect of the gilding jacket on 12.7 mm armour-piercing projectile penetration of armour materials - Lesmana, D. (Cranfield University, 2018)
The influence of both the bullet jacket and projectile core hardness for 12.7-mm armour piercing (AP) rounds has been investigated using a variety of different experiments with the aim of optimising projectile performance. The research was designed to elucidate the role of these two elements in the penetration process, building on work elsewhere in the literature. A combination of forwards and reverse (target impacting stationary projectile) investigations provided insight into both penetration efficiency and resultant target failure modes. The results of these experiments, backed by a pressure-gauge based impact technique, were validated via numerical modelling. It was observed that the jacket appears to serve three inter-linked functions: pre-damage of the target; cushioning of the AP core and confinement of the core. Modifying the core hardness showed that penetration efficiency was maximised when this hardness was greater than / overmatched that of the target (Armox Advance) plate. This behaviour was more pronounced when a thicker (9 rather than 5-mm thick) target plate was employed, suggesting that projectile / target interaction time was of particular importance (a potential confinement effect). However, for the 9-mm target plates where overmatch did not occur, reduced penetration / a ‘ceramic-like’ response was observed. In a similar manner, the presence of a jacket had the greatest effect for thicker plates. However, this confinement effect was complemented by pressure gauge results which suggested that the presence of the jacket enhanced energy coupling into the target (and, in corollary, that the jacket prevented premature and excessive loading of the core). In turn, numerical simulations provided further evidence that the jacket appeared to be protecting (cushioning) the core on impact. However, these also highlighted the extent of pre-damage caused by the jacket.
© Cranfield University, 2018
Keywords: Reverse ballistics; Gas guns; Numerical simulation